An algorithm to form balanced and diverse groups of students - Yeoh, H.K.; Nor, M.I.M. (John Wiley & Sons, 2011)
We share the details of a simple algorithm which groups students based on diversity in gender and race while keeping the group average CGPA nearly equal. Application on simulated and actual class profiles gave multiple-feasible solutions within seconds, with a maximum absolute deviation in group average CGPA of 0.03/4.00 or lower. (C) 2009 Wiley Periodicals, Inc. Comput Appl Eng Educ 19: 582-590, 2011; View this article online at wileyonlinelibrary.com/journal/cae